Financial Management Strategies to Increase Company Profitability - Nurul Masithoh (Universitas Muhammadiyah Palu, 2024)
Effective financial management is a critical factor in fostering a company's growth and long-term sustainability. By managing finances properly, a company can boost profitability, ensure operational stability, and create lasting value for its stakeholders. This article explores a variety of financial management strategies that businesses can implement to increase their profitability. The key areas of focus include managing cash flow, controlling costs, making sound investment decisions, and handling debt efficiently. It is anticipated that by adopting these strategies in a structured and thoughtful manner, companies can maximize their profits and strengthen their competitive position in the market.